PENGARUH KEPADATAN SUBSTRAT PERIFITON TERHADAP PERTUMBUHAN, SINTASAN DAN PRODUKSI BIOMASSA IKAN NILA SALIN (Oreochromis niloticus) DI TAMBAK - Campu, Andi Awal; Malik, Andi Adam; -, Khairuddin; -, Harsani (Jurnal Ilmiah Ecosystem, 2020)
This study aims to determine the effect of periphyton substrate density on the growth, survival, and production of tilapia saline (Oreochromis niloticus) biomass. This research was conducted for one month from January to February 2019 in the Soppeng Riaja District, Barru Regency, South Sulawesi Province. The containers used were 12 units of hapa-installed ponds (1x1m2). Periphyton substrate uses bamboo stems 8 cm in diameter and 1.2 m long. Then bamboo stems were stuck in each treatment except control. The design used was a completely randomized design (CRD) with 4 treatments and 3 replications. The results showed that the best weight growth was obtained in treatment D (72.2 grams / fish), C 42.5 grams / fish), B (28.3 grams / fish) and A (22.3 grams / fish), and growth the best length was obtained in treatments D (12.2cm), C (8.1cm), B (5.4cm) and A (4.4cm). Whereas the best survival rate was obtained in treatments D (96%), C (92%), B (88%) and A (84%), and the best saline tilapia biomass was obtained in treatment D (1.73 kg / m2), C (0.98 kg / m2), B (0.62 kg / m2) and A (0.47 kg / m2). Be concluded that different substrate densities affect the growth, survival, and biomass production of saline tilapia.